(3eHGOF GdJShjb GdMOjK (B:s (3eONd TGed (B/s - (3GdWGFj, MejOs; (3GdYdGb, HTjQ s ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2009)
(3eONd Gdi GdJShjb , GdHjFI GdJShjbI , JLRFI GdShb h JMOjO GdGShGb GdeSJgOaI , Sdhc GdeSJgdc , JShjb GdNOeGJ , GdJSYjQ , GdJhRjY , GdJQhjL , h GNjQG GdJShjb GdGdcjQhfj(B.s
(3eQGLY (B: (3dcd aUd eQLYs
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3GdJShjb GdEdcJQhfjs